Effects of Self-Concept, Discipline, and Institutional Context on Academics' Professional Identities at a South African University - Folabit, Novel Lena; Jita, Loyiso C (Journal of Ecohumanism, 2024)
This study investigates how academics’ self-concept, disciplinary background, and institutional context shape their professional identities at a South African university. This qualitative case study research conducted semi-structured interviews with eight university lecturers. The academics were chosen using convenience sampling based on accessibility and willingness to share their experiences. Thematic analysis was applied to identify patterns and themes related to the academics' professional identities. The reciprocal determinism theory framed the study. The study found that a positive self-concept, including confidence, motivation, and engagement, encourages academics to pursue their professional roles ambitiously, while self-doubt hinders professional growth. It also found that meeting disciplinary and institutional expectations, such as administrative workload, H-Index publication pressure, and adapting to new technologies, creates tension as academics balance multiple responsibilities while striving to meet institutional standards. These factors interact to shape how academics see and fulfil their professional roles. The study emphasises the importance of creating supportive institutional environments that recognise and address the various factors influencing academics' professional identities. By promoting a positive work environment, fair compensation, and professional development opportunities, institutions can improve the work-life quality and commitment of academic staff, ultimately contributing to the development of their professional identities.